PENGARUH KOMPENSASI DAN KOMPETENSI MELALUI KUALITAS LAYANAN TERHADAP KINERJA PERUSAHAAN SEPEDA MOTOR KELAS 150 CC DI KOTA PEKANBARU PROVINSI RIAU - Arifin, Arifin; Zulfadil, Zulfadil; Rosyetti, Rosyetti (Jurnal Tepak Manajemen Bisnis, 2018)
This study aims at acknowledging the influence of Compensation andCompetence through Service Quality toward the Cinergy of MotorcycleCompanies Class 150 Cc in Pekanbaru. The target of the study is all dialers ofPT. Astra Honda Motor, PT. Yamaha Indonesia Motor Manufacturing and PT.Kawasaki Motor Indonesia located in Pekanbaru Metropolitan. The problem ofthe research is the salary and education qualification of sellers which showpositive value every year, but the companiesâ activities decrease from 2014 to2016.The population are all dialer sellersâ68 persons. All population and 340costumers become the sample of the research. Every variable is examined inorder to determine the level of direct and indirect influence toward the cinergy ofthe company (the quality of service) by using smart PLS 3.0.The research findings show that compensation and competence of servicequality, partially has positive and significant influence toward the cinergy of thecompany. On the other hand, the compensation and competence show indirectinfluence significantly toward the cinergy of the company through the quality ofservice..